Evaluating Knowledge Co-Creation Within One Dentsu: Collaboration and Governance in Dentsu Indonesia - Cindy Vera Gita Kencana; Achmad Ghazali (Green Publisher Indonesia, 2025)
This research is based on the problem that although One Dentsu has been strategically adopted, in Indonesia this initiative has not been fully internalized in the daily working process. One of the main challenges is the absence of a systematic Knowledge Co-Creation (KCC) mechanism and a formal organizational governance structure that supports cross-functional collaboration. This research uses a qualitative approach with a single case study method. Data were collected through in-depth interviews with five respondents who are key stakeholders of strategic service units in Dentsu Indonesia, specifically those with a strategic role in One Dentsu. This research uses Knowledge Co-Creation (KCC) theory as the main framework, which includes four main phases: knowledge donating, knowledge collecting, knowledge replication, and network citizenship. Aside from that, Knowledge Governance theory is also used to evaluate how far the organizational structure supports or hinders the KCC process, as well as to identify governance strategies currently in place. The results of the research show that the KCC process in Dentsu Indonesia takes place informally and in an unstandardized manner. Every individual has a different understanding of the meaning of One Dentsu, and there is no formal training or guidance that explains how to implement it comprehensively and in detail. In practice, the implementation of cross-functional collaboration occurs spontaneously and often depends on personal initiatives rather than organizational systems.